Identification of staphylococcal phage with reduced transcription in human blood through transcriptome sequencing - Santiago-Rodriguez, Tasha M.; Naidu, Mayuri; Jones, Marcus B.; Ly, Melissa; Pride, David T. (Frontiers in Microbiology, 2015)
Many pathogenic bacteria have bacteriophage and other mobile genetic elements whose activity during human infections has not been evaluated. We investigated the gene expression patterns in human subjects with invasive Methicillin Resistant Staphylococcus aureus (MRSA) infections to determine the gene expression of bacteriophage and other mobile genetic elements. We developed an ex vivo technique that involved direct inoculation of blood from subjects with invasive bloodstream infections into culture media to reduce any potential laboratory adaptation. We compared ex vivo to in vitro profiles from 10 human subjects to determine MRSA gene expression in blood. Using RNA sequencing, we found that there were distinct and significant differences between ex vivo and in vitro MRSA gene expression profiles. Among the major differences between ex vivo and in vitro gene expression were virulence/disease/defense and mobile elements. While transposons were expressed at higher levels ex vivo, lysogenic bacteriophage had significantly higher in vitro expression. Five subjects had MRSA with bacteriophage that were inhibited by the presence of blood in the media, supporting that the lysogeny state was preferred in human blood. Some of the phage produced also had reduced infectivity, further supporting that phage were inhibited by blood. By comparing the gene expression cultured in media with and without the blood of patients, we gain insights into the specific adaptations made by MRSA and its bacteriophage to life in the human bloodstream.